The Role of Social Identity and Perceived Discrimination in Human Capital Formation: Evidence from India - Isha Gupta (Global Labor Organization (GLO), 2022)
This study examines the role of historically defined social identity in human capital development over time by focusing on a region from India where social identities are defined along the lines of castes and religious groups. It investigates the evolution of gaps across social groups in children's cognitive outcomes and parental investment in children's education from ages 5 to 15. Significant gaps in test scores and parental investment are found between children from lower and upper Hindu castes. These gaps, which originate early in childhood and persist throughout the 10 years of the study period, cannot be completely explained by the differences in socioeconomic status across social groups. Moreover, the perception of social discrimination is also found to be a significant contributor to the gaps in cognitive outcomes and parental investment across social groups. While parents' perceived social discrimination is associated with lower parental investment throughout childhood, it is negatively associated with children's cognitive outcomes only at later ages.
Keywords: I24; J15; J24; 330; child development; parental investment; human capital formation; social identity; caste; perceived social discrimination; India